2021
DOI: 10.1155/2021/3730963
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Terpenoid Natural Chinese Medicine Molecular Compound on Lung Cancer Treatment

Abstract: Among all malignant tumors in the whole universe, the incidence and mortality of lung cancer disease rank first. Especially in the past few years, the occurrence of lung cancer in the urban population has continued to increase, which seriously threatens the lives and health of people. Among the many treatments for lung cancer, chemotherapy is the best one, but traditional chemotherapy has low specificity and drug resistance. To address the above issue, this study reviews the five biological pathways that commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 106 publications
0
7
0
Order By: Relevance
“…Many of them have pharmacological activitiesanticancer, antimicrobial, and anti-inflammatory. , Because of their diversity and interesting properties, they have become important ingredients in food, cosmetics, and pharmaceuticals. Their chemical synthesis is usually unprofitable or unsustainable, so efficient extraction from natural sources seems to be a very important direction in research and industrial development. Table presents a few examples of terpenes and terpenoids, with their activities and possible applications. , …”
Section: The Most Interesting Bioactive Compounds Extracted With Dess...mentioning
confidence: 99%
“…Many of them have pharmacological activitiesanticancer, antimicrobial, and anti-inflammatory. , Because of their diversity and interesting properties, they have become important ingredients in food, cosmetics, and pharmaceuticals. Their chemical synthesis is usually unprofitable or unsustainable, so efficient extraction from natural sources seems to be a very important direction in research and industrial development. Table presents a few examples of terpenes and terpenoids, with their activities and possible applications. , …”
Section: The Most Interesting Bioactive Compounds Extracted With Dess...mentioning
confidence: 99%
“…A report made by the University of North Carolina at Chapel Hill Lineberger Comprehensive Cancer Center in the United States revealed that 76.8% of lung cancer patients had received CAM treatment after diagnosis [10]. As a representative type of CAM, traditional Chinese medicine (TCM) plays a significant role in health maintenance in China and parts of East Asia [11][12][13]. TCM is the collective name of medicine of all nationalities in China, including Chinese and minority medicine, and is a system of medicine that reflects the Chinese nation's understanding of life, health, and disease, with a long historical tradition and unique theories and technical methods.…”
Section: Introductionmentioning
confidence: 99%
“…Several achievements have been made in the research and development of traditional Chinese medicines with anti-cancer potential [4]. However, at present, most of the studies are based on compound therapy.…”
Section: Introductionmentioning
confidence: 99%